ANALISIS SPASIAL PENGARUH FAKTOR LINGKUNGAN TERHADAP PERSEBARAN KASUS MALARIA DI KECAMATAN PUNGGELAN KABUPATEN BANJARNEGARA - Desi Tri Puspaningrum; Mursid Rahardjo; Nurjazuli Nurjazuli (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Malaria is still a health problem in the world. There is about 3.3 billion citizens from 97 countries has been infected by malaria disease. In Indonesia, there are about 54% from 497 districts becoming endemic area of malaria disease. Banjarnegara becomes one of the endemic area in Central Java Province. Banjarnegara has four sub-district are with high cases of malaria. The area of sub-district, Punggelan has the API value 1,12/1000 citizens. It does not reach national target which is targeting API <1/1000 citizens, yet. The purpose of this research is analyzing spatial distribution and knowing the influence of environmental factors toward malaria disease in sub-district Punggelan, Banjarnegara in 2015. The type of this research is analytical observational with control cases design using simple random sampling technique. The amount of sample is 120. Bivariate analysis using chi square test and spatial analysis using Arcgis 9.3. software. Bivariate test result of each independent variabel incidence of malaria as follow: the presence of puddles (p = 0.022; OR = 2.962), the presence of wire netting (p = 0,0001; OR = 42), the condition of house wall (p = 0.0001; OR = 11.811), and the presence of ruminants (p = 0.031; OR = 0.381). Spatial analysis shows the distribution of malaria cases are in the majority around a puddle with a distance up to 300 m, cases of malaria in Punggelan near the ruminants, caught malaria mosquitoes that An. aconitus, An. maculatus, An. balabacensis. This research can be concluded that the presence of puddles, the presence of wire netting, the condition of house wall, and the presence of ruminants relating to malaria disease in the Punggelan subdistrict.